Complications and blood loss after invasive treatments for small renal masses: A systematic review - Kandi, Maryam; Richard, Patrick O.; Violette, Philippe D.; Sreekanta, Ashwini; Hanna, Steven; Couban, Rachel; Daza, Julian; Leong, Russell; Faisal, Haseeb; Tamilselvan, Divyalakshmi; et al. (Canadian Urological Association Journal, 2024)
INTRODUCTION: This systematic review and meta-analysis provides estimates of major complications and estimated blood loss (EBL) for open partial nephrectomy (OPN), conventional laparoscopic partial nephrectomy (LPN), and robot-assisted partial nephrectomy (RAPN). Additionally, it outlines the incidence of major complications associated with percutaneous thermal ablation (TA) in patients with small renal masses (SRMs). METHODS: We searched MEDLINE, EMBASE, and CINAHL from inception to the end of July 2023. We supplemented the electronic search with a hand search of the references in the included studies and suggestions from two content experts. We used random effect meta-analysis to obtain pooled estimates of major complications and EBL. We used the QUIPS tool for risk of bias assessment and applied a prognosis approach to rate the quality of evidence using the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) framework. RESULTS: We included 65 eligible studies that provided pooled estimates of major complications after OPN of 5.4% (95% confidence interval [CI] 2.9–9.9); after conventional LPN of 4.7% (95% CI 2.6–8.3); after RAPN of 2.9% (95% CI 2.2–3.7); and after TA of 2.5% (95% CI 1.7–3.6). Pooled estimates demonstrating mean EBL of 262 ml (95% CI 200–324) for OPN; 224 ml (95% CI 193–254) for conventional LPN; and 163 ml (95% CI 136–190) for RAPN. CONCLUSIONS: This review provides the best available estimates of major complications and mean EBL after partial nephrectomy in patients with SRMs.